Mesenteric lymphadenopathy in children with recurrent abdominal pain - Sabal, Saransh; Poswal, Lakhan; Gediya, Sandip; Goyal, Suresh (International Journal of Contemporary Pediatrics, 2017)
Background: Enlarged mesenteric lymph nodes (MLN) are frequently seen in children with abdominal pain and in the absence of other disorders, have been attributed to primary mesenteric lymphadenitis. Mesenteric lymphadenitis is commonly reported in children with acute, chronic or recurrent abdominal pain and no evidence of other pathologies. The purpose of this study was to find out the association of USG finding of enlarged mesenteric lymph nodes with causation of recurrent abdominal pain and outcome of these patients on follow up. Methods: This hospital based prospective study was done on 82 patients aged 5 to 15 years, attending Bal Chikitsalaya, RNT Medical college, Udaipur, fulfilling Apley’s criteria of RAP. Detailed history, physical examination, relevant investigations and USG abdomen was done in all patients. Results: Eighty-two children were enrolled; out of which majority (62.19%) were in age group 5-8 years with mean age 7.9±2.69 years. Mesenteric lymphadenopathy was found in 14 (17.07%) cases. All patients with mesenteric lymphadenopathy 14 (100%) had periumbilical pain and diurnal variation of pain. Follow up of 14 patients who had mesenteric lymphadenopathy showed that in 12 (85.71%) patients, the mesenteric lymphadenopathy resolved on USG despite that pain abdomen persisted in 7 (58.33%). Conclusions: The presence of mesenteric lymphadenopathy can’t be attributed to recurrent abdominal pain.